Legal Functionalization of Integrated Service Institutions Empowering Women and Children (P2TP2A) In the Prevention, Handling, And Assistance of Victims of Violence Against Women And Children in The Cianjur Regency - Mia Amalia; Nahknur Wudhi Ainnaiha; Arti Aneja; Ibrahim Sule (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
The eradication of violence against women and children is one of the benchmarks for the success of regional development. Many cases of violence can be handled by the government, which is represented by the Integrated Service Center for the Empowerment of Women and Children (abbreviated: P2TP2A). The purpose of this study is to analyze how the tasks, functions, and obstacles faced by P2TP2A Cianjur Regency, as an institution appointed by the local government in the prevention and prosecution of women and children who are victims of violence in Cianjur Regency and the efforts made by the local government to support P2TP2A, to be used as an evaluation to be even better in its functionalization. The method in this study uses a normative juridical and sociological juridical approach with descriptive research specifications. It uses data analysis, namely qualitative normative analysis, in that the data obtained will be arranged systematically for further qualitative analysis. Based on the results of this study, it is known that there are rampant cases of violence against women and children as victims in the Cianjur Regency. To overcome this, P2TP2A Cianjur Regency provides services for victims, including prevention programs and enforcement programs (curative and rehabilitative). The enforcement program here focuses on assisting victims, where there are three types of assistance: medical help, psychological juridical aid, and service. In implementing these programs, several obstacles were found that became obstacles that must be resolved immediately. One of them is the low level of attention and commitment of the Cianjur Regency Government in supporting the implementation of P2TP2A programs both materially and immaterially.